2009
DOI: 10.1007/978-3-642-01516-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Adding GPS-Control to Traditional Thermostats: An Exploration of Potential Energy Savings and Design Challenges

Abstract: Abstract. Although manual and programmable home thermostats can save energy when used properly, studies have shown that over 40% of U.S. homes may not use energy-saving temperature setbacks when homes are unoccupied. We propose a system for augmenting these thermostats using just-in-time heating and cooling based on travel-to-home distance obtained from location-aware mobile phones. Analyzing GPS travel data from 8 participants (8-12 weeks each) and heating and cooling characteristics from 5 homes, we report r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 10 publications
0
65
0
Order By: Relevance
“…Specifically, BALANCE is useful to those with a strong desire to keep their energy bill below a certain amount and who are willing to relax their ideal comfort requirements. We demonstrated that our simple BalancingAgent can reliably meet a reasonable user-provided budget 7 and provide at least a 40% improvement in comfort over the lowest-cost approach, given user preferences. There are also several avenues for improving the performance of the BALANCE agent that have the potential to meet the budget with more time spent in the preferred comfort range.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, BALANCE is useful to those with a strong desire to keep their energy bill below a certain amount and who are willing to relax their ideal comfort requirements. We demonstrated that our simple BalancingAgent can reliably meet a reasonable user-provided budget 7 and provide at least a 40% improvement in comfort over the lowest-cost approach, given user preferences. There are also several avenues for improving the performance of the BALANCE agent that have the potential to meet the budget with more time spent in the preferred comfort range.…”
Section: Discussionmentioning
confidence: 98%
“…Several applications have been developed to enable control of a thermostat using a cell phone (Figure 3). Global Positioning Systems (GPS) in cell phones have been used to convey occupancy to smart thermostats, which can then predict arrival times of a home's occupants and modify the setpoint accordingly (Gupta, Intille, & Larson, 2009). An "Internet thermostat" describes a programmable thermostat that connects to an IP (Internet Protocol) network; models are currently being made by Proliphix, Aprilaire, and Ecobee (Figure 3).…”
Section: Networked Thermostatsmentioning
confidence: 99%
“…Parker, Barkaszi, Sherwin, & Richardson, 1996;Rathouse & Young, 2004b) Aesthetics of the device (Gupta, et al, 2009) People want to retain control (Kempton, Reynolds, Fels, & Hull, 1992) Special HVAC systems (Evaporative Cooling, Heat Pumps) work differently than normal systems and require a different operating mode, user practice, and (Bouchelle, et al, 2000;Diamond, et al, 1996) thermostat setting High priority for heating in people's expenditures (Rathouse & Young, 2004b) Renter/Owner problem In some studies, functions like the "boost button" (an additional hour of heating (Rathouse & Young, 2004b), a timer (Kempton, Feuermann, & McGarity, 1992), and indication of the time needed to reach the desired temperature (Karjalainen, 2008) were considered useful to customers. These features are not currently available in any of the surveyed U.S. thermostats.…”
Section: Barriers To Using Pts Referencesmentioning
confidence: 99%
See 2 more Smart Citations